The Critical in Critical Pedagogy: The Interface between Challenges and Opportunities - Panthi, Badri Narayan (Journal of Tilottama, 2023)
The paper aims at examining the fundamental premises of critical pedagogy as advocated by key theorists among others Paulo Freire, Henry Giroux and bell hooks. In doing so, it examines the major pitfalls and opportunities of critical pedagogy in the classroom context. The paper also examines the current scenario of higher education with the neoliberal hegemony. Finally, the paper examines the present state of quality education in Nepal. The paper concludes that implementation of critical pedagogy principles in the classroom can foster a learning environment that prioritizes student agency and empowerment. By encouraging students to question dominant narratives and perspectives, the teacher in this study created opportunities for students to express their own perspectives and develop their own critical thinking skills. The teacher also fostered a strong sense of community in the classroom, with students and the teacher collaborating and supporting each other in their learning.